Estradiol enhances T-type calcium channel activation in human myometrium telocytes - Lin ZHU; Tao SHANGGUAN; Penghui CHEN; Ying WANG; Lan XIAO; Heying LIU; Wei HE (The Society for Reproduction and Development, 2023)
Uterine peristalsis is essential for gamete transport and embryo implantation. It shares the characteristics of spontaneity, rhythmicity, and directivity with gastrointestinal peristalsis. Telocytes, the "interstitial Cajal-like cells" outside the digestive canal, are also located in the uterus and may act as pacemakers. To investigate the possible origin and regulatory mechanism of periodic uterine peristalsis in the human menstrual cycle, telocytes in the myometrium were studied to determine the effect of estradiol on T-type calcium channel regulation. In this study, biopsies of the human myometrium were obtained for cell culture, and double-labeling immunofluorescence screening was used to identify telocytes and T-type calcium channel expression. Intracellular calcium signal measurements and patch-clamp recordings were used to investigate the role of T-type calcium channels in regulating calcium currents with or without estradiol. Our study demonstrates that telocytes exist in the human uterus and express T-type calcium channels. The intracellular Ca2+ fluorescence intensity marked by Fluo-4AM was dramatically decreased by NNC 55-0396, a highly selective T-type calcium channel blocker, but enhanced by estradiol. T-type calcium current amplitude increased in telocytes incubated with estradiol in a dose-dependent manner compared to the control group. In conclusion, our study demonstrated that telocytes exist in the human myometrium, expressing T-type calcium channels and estradiol-enhanced T-type calcium currents, which may be a reasonable explanation for the origin of uterine peristalsis. The role of telocytes in the human uterus as pacemakers and message transfer stations in uterine peristalsis may be worth further investigation.